PTU-332 Five-year review of local hepato-pancreatobiliary (hpb) cancer service and its impact on cancer detection in a non-tertiary centre in mersey region. (22nd June 2015) - Lekharaju, VPK; Boon, A; Redwood, A; Singhal, A
Abstract : Introduction: Management of patients with HPB cancer is complex. This requires close liaison between secondary and tertiary centres. Care of HPB cancer patients is limited by variable expertise of respective clinical teams. We developed a local HPB Cancer Service (HPBCS) in 2008 to improve the quality of care and hereby report 5-year impact on referrals to HPBCS. Method: Local HPB Service: The HPBCS was launched on the Wirral in June 2008, first such service in a large DGH (catchment population of 360 000) in Merseyside. Patients with suspected HPB cancer were referred to the local HPBCS comprising of 2 HPB consultants and specialist nurse. Patients are identified via 2-week referrals from primary care, acute admissions, ward referrals and radiology flags. All patients are managed as per regional Mersey and Cheshire Cancer Network (MCCN) protocols with discussion at the appropriate MDTs. The team meets weekly to discuss all new referrals, MDT outcomes and care of all sick patients. There are weekly HPB nurse-led outpatient and telephone clinics that provide urgent feedback of MDT decisions, rapid access for symptom control and ensures continuity of care. The demographics, imaging reports and MDT outcomes are prospectively collected and maintained in a database. We reviewed and analysed the data for the last 5 years since the set up of the HPBCS. Results: There is an year on year increase in cancer detection and referral rates since establishing the local HPBCS. The cohort of patients requiring annual surveillance for IPMN is continously increasing. We are the major feeder hospital to supra-regional MDTs. Table 1 summarises the work load and referral numbers. Conclusion: Since commencement of HPBCS, there is definite increase in number of suspected HPB cancers within the trust. These are referred on to the regional MDTs within 2 weeks, resulting in timely and uniform care as per MCCN guidelines, with local ownership of care. There is consistent rise in diagnosis of hepatocellular cancer which may reflect increasing incidence of chronic liver diseases nationally. Ever increasing pool of surveillance patients and radiology alerts contribute to significant ongoing work load. HPBCS was formally praised in MCCN peer review in 2010 and awarded Wirral Trust Foundation Award in 2011. Disclosure of interest: None Declared.